2018
DOI: 10.20965/jdr.2018.p0740
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Etiological and Epidemiological Study on Acute Respiratory Infections in Children: Providing Evidence for the Prevention and Control of Childhood Pneumonia in the Philippines

Abstract: Childhood pneumonia has been the leading cause of morbidity and mortality for decades. Although substantial progress in the understanding of risk factors and etiology of pneumonia has been made, childhood pneumonia remains the major cause of death in children, accounting for 900,000 of the estimated 6.3 million child deaths worldwide in 2013. More than 90% of all episodes of clinical childhood pneumonia worldwide occur in low and middle-income countries. More effective and feasible interventions need to be dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In the previously described prospective cohort study, 24,25 a cohort of 4012 children younger than 5 years old was followed in two municipalities, Kawayan and Caibiran, on a main island of Biliran province in the Philippines, from March 2014 to June 2016. From this larger data set, we focused on respiratory tract illness (RTI) episodes identified at health facilities over a time window of exactly 2 years, between April 2014 and March 2016.…”
Section: Methodsmentioning
confidence: 99%
“…In the previously described prospective cohort study, 24,25 a cohort of 4012 children younger than 5 years old was followed in two municipalities, Kawayan and Caibiran, on a main island of Biliran province in the Philippines, from March 2014 to June 2016. From this larger data set, we focused on respiratory tract illness (RTI) episodes identified at health facilities over a time window of exactly 2 years, between April 2014 and March 2016.…”
Section: Methodsmentioning
confidence: 99%
“…A prospective cohort study on ARIs was conducted in Biliran Island, the Philippines, from March 2014 to June 2016, the details of which are described elsewhere [9,11,12]. Children in the study area, two municipalities (Caibiran and Kawayan) on the island, were identified by a census and household visitation, and children less than five years of age there were recruited for the cohort study.…”
Section: Cohort Study Designmentioning
confidence: 99%
“…We have conducted a cohort study of children with ARI at both the household and healthcare facility levels as well as performed a hospital-based study of severe hospitalized patients with ARI in the Philippines [11]. The data analysis of those studies has uncovered risk factors for the incidence and mortality of ARIs [9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This paper is part of a larger study that looked into Acute Respiratory Infections in children. 23 A prospective cohort study was conducted in Biliran, an island province located between the islands of Leyte and Samar in the Eastern Visayas region in the Philippines, with a total population of 161,760. 24 It is classified as a fourth-class province, with a predominantly agriculture and fishery economy and is considered as one of the poorest provinces in the country.…”
Section: Study Sitementioning
confidence: 99%
“…It was chosen as the study site due to its relatively stable population migration patterns and simple health referral system. 23 The map in Figure 1 Figure 1 shows locations of municipalities of Kawayan and Caibiran, where the study took place. Based on the results of a rapid assessment study, 5 the expected incidence of childhood pneumonia/year and severe pneumonia/year are 400 and 250, respectively.…”
Section: Study Sitementioning
confidence: 99%